International Scholarships and Southern Agency: An Ethnography of Alumni, Scholars, and Applicants. (May 2023) - King, Monty; Forsey, Martin; Pegrum, Mark
International scholarships are an established mode of aid distribution for many donor countries and a life-changing educational opportunity for recipients from the global South. This article draws upon ethnographic field research centred on Dili, Timor-Leste, focussing on case studies of a scholarship applicant, a scholar, and an alumnus. It employs the concept of Southern agency, investigating individual practices shaped by influences that both constrain and enable action, namely local infrastructure, family and kinship groups, literacies, and the colonial legacy. Scholarship places are limited and extremely competitive, while assigning a moral imperative for alumni to learn and return to contribute to local development, often resulting in the re-production of socially normed roles echoing the colonial era. The global upheaval in higher education resulting from the COVID-19 pandemic emphasises the need for alternative interventions in the global South, including greater investment in local higher education institutions, and online learning.